The Impact of Modern Technologies on Women's Empowerment: A Case Study of Online University - Rana Rahman; Falaknaz Asadi; Rabia Ghory; Shafiqa Popalzay; Tamanna Quraishi (Tinta Emas Publisher, 2025)
This study investigates the impact of modern technologies on women's empowerment through online education, focusing on their access to higher education, career advancement, and social engagement. The purpose of the research is to understand how digital tools, including smartphones, e-learning platforms, and social media, facilitate women's participation in education and employment, particularly in developing regions. A total of 110 participants from four academic faculties—Medical, Computer Science, Economics, and Education—were surveyed using a structured questionnaire to assess the effectiveness of these technologies in empowering women. The results indicate that technologies such as online learning platforms, mobile devices, and social networking tools have positively influenced women's educational opportunities and career development. However, barriers such as limited access to digital resources, socio-cultural restrictions, and inadequate digital literacy were also identified as challenges. The findings suggest that online education, when accessible and well-implemented, significantly contributes to women's social empowerment and participation in digital economies. Despite these positive outcomes, there is a need for targeted interventions to address the existing technological and socio-cultural barriers, ensuring that more women can benefit from the opportunities provided by modern technologies. In conclusion, while the integration of digital tools has shown promising potential for empowering women, further efforts are required to overcome persistent challenges and fully unlock the transformative power of technology in advancing gender equality.